ANALYSIS OF THE FREQUENCY OF SPECIFIC POSTOPERATIVE COMPLICATIONS IN PATIENTS WITH DIFFUSE TOXIC GOITER DEPENDING ON THE METHOD OF SURGICAL TREATMENT (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2022)
The authors analyze the frequency of specific complications and the main causes of the complicated course of the early and late period after surgical treatment of DTG.The authors conclude that the use of the improved method of surgical access to the thyroid gland and the postoperative rehabilitation program made it possible to reduce the incidence of long-term complications, which, in general, provided an increase in the proportion of good and satisfactory results from 84.7% to 97.3% with a decrease in the probability of an unsatisfactory outcome from 15.3% to 2.7%.